Empowerment of Basic and Digital Literacy for Enhancing Socio-Economic Capacity in Sukoharum Village: Pemberdayaan Literasi Dasar dan Digital untuk Peningkatan Kapasitas Sosio-Ekonomi di Desa Sukoharum - M. Reza Saputra; Nabila Hilyatunisa (Yayasan Cerdas Pedia Indonesia, 2025)
This community service research focuses on addressing the dual literacy gap basic and digital through an integrated intervention in Sukoharum Village, Adiluwih Subdistrict, Pringsewu Regency, Lampung. Despite possessing significant socio-economic potential, the village faces limited access to formal education and digital skills. The Community Service Program (KKN) was conducted from August 1–31, 2025, employing the Community-Based Participatory Research (CBPR) approach through stages of social mapping, participatory planning, implementation, and mentoring. Core activities included the establishment of a “Reading Corner” for children, Microsoft Word training, and digital marketing outreach for youth and Islamic boarding school students. Evaluation was carried out using quantitative participation data and qualitative observations of behavioral changes. The findings indicate enhanced reading interest among children, improved document processing skills among youth, and a greater understanding of local product marketing strategies through social media. The synergy of basic and digital literacy has shaped a sustainable empowerment model, reinforcing human resource capacity as the foundation for the village’s socio-economic development.